Lamp monitoring system for classroom in FSKKP using NodeMCU ESP8266 - Nadhiah, Mat Yusof (2019)
Lamp monitoring system is the smart room system where this system helps to manage the lighting in the classroom. This system using NodeMCU ESP8266 as a hardware component. The purpose of this system is to reduce the time especially for technician and secure the classroom from the violation and protect facilities in the classroom. Currently, the classroom in the Fskkp have been monitored by technician with their own website which contains features of booking lab/class. Each of the technician, should monitor the lab/class every day to make sure all the facilities are in good condition. But, there is a problem in lab/class where students/lecturer always forgot to switch off the lamp. The technician will switch off the lamp manually and this will demand extra work for the technician. Thus, this proposed system will cater the problem by automatically switch off/on the lamp. This system will being develop to monitor the lamp in the classroom with using the interface for user to use this system. The system using system model Rapid Application Development (RAD) for develop the proposed system. In the methodology shows how the planning of project, analysis, design, implementation and maintenance for this system. By developing this system, the technician can use the system with more manageable and systematic.